126k views
5 votes
Please help ASAP 50 points :(((

Please help ASAP 50 points :(((-example-1
User Mortensi
by
5.9k points

2 Answers

7 votes

Answer:

(f o g) (x) = 36x² + 3

(g o f) (x) = 6x² + 18

Explanation:

f(x) is x² + 3

g(x) is 6x

(f o g) (x) means for all xs in f replace it with g(x) or 6x

(f o g) (x) = (6x)² + 3 - see 6x is in place of x and 6x is g(x)

(f o g) (x) = 36x² + 3

(g o f) (x) = 6(x² + 3)

(g o f) (x) = 6x² + 18

User Jonathan Evans
by
5.2k points
0 votes

Answer:

f(g(x)) = 36x^2+3

g(f(x)) = 6x^2+18

Explanation:

f(x) =x^2+3

g(x) =6x

f°g(x) = means put g(x) in for x into the function f(x)

f(g(x)) = (g(x))^2 +3

(6x)^2 +3

36x^2+3

g°f(x) = means put f(x) in for x into the function g(x)

g(f(x)) = 6(f(x)

6(x^2+3)

6x^2+18

User Dukens
by
5.6k points